2022
DOI: 10.1007/s12310-022-09528-z
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Perceptions of Implementation Climate Related to Feasibility of Implementing Schoolwide Positive Behavior Supports and Interventions

Abstract: For Schoolwide Positive Behavior Interventions and Supports (SWPBIS) to be effective, educators must use the practices as intended. Whether a teacher uses a practice as intended can depend, in part, on how feasible the practice is perceived to be. Identifying malleable factors associated with teachers’ perceptions of SWPBIS feasibility can help schools identify targeted supports to improve feasibility. Implementation climate, or the shared perception among implementers that their school supports implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
4
4
0
Order By: Relevance
“…Although the classroom teacher was identified as a tool agent in 28% of the programs, this study found that 50% of staff members were engaged in the program, leading to positive outcomes. This finding is consistent with the study of Corbin et al (2022), who reported that when schools include educators and staff members such as school psychologists, special educators, and paraeducators, their responsibilities can differentially impact students' behavioral outcomes. In addition, staff members who leverage shared time to resolve behavioral issues and integrate SWPBIS with academic instruction can influence the successful outcome of classroom instruction and student behavior (Corbin et al 2022).…”
Section: Tool Agentssupporting
confidence: 91%
“…Although the classroom teacher was identified as a tool agent in 28% of the programs, this study found that 50% of staff members were engaged in the program, leading to positive outcomes. This finding is consistent with the study of Corbin et al (2022), who reported that when schools include educators and staff members such as school psychologists, special educators, and paraeducators, their responsibilities can differentially impact students' behavioral outcomes. In addition, staff members who leverage shared time to resolve behavioral issues and integrate SWPBIS with academic instruction can influence the successful outcome of classroom instruction and student behavior (Corbin et al 2022).…”
Section: Tool Agentssupporting
confidence: 91%
“…The measurement invariance of the IBA across teachers in different implementation roles and with different implementation experiences should be evaluated. Further, future research could evaluate if psychometric properties change if the general term “intervention” is replaced by a specific intervention name; a recent study documented limited impact of wording changes in sample of teachers’ rating items around school-based implementation (Corbin et al, 2022). Future research could take a different approach by conducting an exploratory CFA instead of an EFA given the grounding of the measure in the HAPA model.…”
Section: Discussionmentioning
confidence: 99%
“…Future research could take a different approach by conducting an exploratory CFA instead of an EFA given the grounding of the measure in the HAPA model. The IBA includes only a small number of factors; although these were specifically chosen due to their alignment with the HAPA, future research should evaluate the associations between these factors and other individual- and organizational-level determinants that can be reliability measured and demonstrate utility in practice (Corbin et al, 2022; Lyon et al, 2018). Further, there is an uneven number of items across the IBA factors, with considerably more items in the Implementation Self-Efficacy subscale; future research may evaluate options for more even subscales, and implications in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, being able to implement SWPBIS with fidelity may improve student outcomes (Bastable et al, 2020) and improve overall school climate (Ellis et al, 2022). When teachers improve confidence in their ability to use a framework like SWPBIS, there is an enhancement in teacher ability to manage or support student behavior in a sustained manner (Chitiyo et al, 2019; Fox et al, 2022), and, when teachers perceive their school as having a positive climate, they are more likely to report a framework like SWPBIS to be feasible (Corbin et al, 2022). In fact, studies have found teachers perceive the SWPBIS framework to be beneficial to their schools (Chitiyo & May, 2018; McDaniel et al, 2021), that its implementation improves school climate (Charlton et al, 2021; Mitchell et al, 2018), and reduces teacher burnout (Ross et al, 2012).…”
Section: Swpbis and Students With Csnmentioning
confidence: 99%